Effects of void shape and orientation on the elastoplastic properties of spheroidally voided single-crystal and nanotwinned copper. Issue 18 (16th September 2020) - Li, Bin; Mi, Changwen
ABSTRACT: Void nucleation, growth and coalescence have been identified as the leading cause of ductile damage in metallic materials. To understand the underlying deformation and damage mechanisms, extensive theoretical, experimental and simulation efforts have been attempted on spherically voided metals. In this work, molecular dynamics simulations are performed to analyze the uniaxial straining deformation behaviours of both single-crystal and nanotwinned copper materials embedded with a preexisting spheroidal void. The coupling effects among twin boundary, spheroidal void aspect ratio and orientation on unidirectional elastoplastic behaviours are systematically examined. The dislocation-induced plastic deformation mechanism is also examined and compared with the one due to a perfectly spherical cavity. Simulation results show that elastic modulus increases with both spheroidal void aspect ratio and orientation. So do the yield stress, the first peak stress and the plasticity index. Another peak stress exists for most cases, except for a prolate void embedded in nanotwinned specimens. The slope between peak stresses decreases with both the spheroidal aspect ratio and orientation. The incorporation of a twin boundary results in lower elastic modulus, higher yield strength and smaller plasticity index. For an oblate void, the twin boundary gives rise to more severe strain softening behaviour. The dislocation extraction algorithm illustrates that the continuous nucleation, propagation and reaction of dislocations emanated from both the void front and twin boundary are responsible for the ductile damage of spheroidally voided crystals. The lower dislocation densities found in nanotwinned specimens indicate the desired suppression effects of twin boundary on dislocation activities.